EVALUATION HYPOLIPIDEMIC ACTIVITY OF AROGYAVARDHINI AND ZPTER TABLET IN CHOLESTEROL-RICH HIGH FAT DIET (HFD) INDUCED HYPERLIPIDEMIA IN WISTAR RATS - Ghadigaonkar, Dinesh D.; CHAWDA, MUKESH B.; THAKUR, KAPIL S.; KUSHWAH, PAWAN K. (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: The present research work aims to evaluate the hypolipidemic activity of arogyavardhini and zpter tablet in high fat diet (HFD) induced hyperlipidemia in wistar rats. Methods: Wistar rats were divided in 5 groups. The normal control group received standard pellet diet. The HFD group received HFD rich in cholesterol. The HFD+Arogyavardhini group received HFD rich in cholesterol along with Arogyavardhini treatment. The HFD+zpter group received HFD rich in cholesterol along with zpter treatment. The standard Control group received HFD rich in cholesterol and treatment with Atorvastatin. Serum Lipid profile estimation and histopathological estimations done at end treatment. Group means were compared with Analysis of Variance (ANOVA) followed by Tukey‘s post-hoc analysis (P<0.05). Result: HFD group shows significant (P<0.05) increase in total cholesterol (TC) levels (207.15 mg/dl) and triglyceride (TG) levels (223.83 mg/dl) when compared with standard pellet fed rats (TC=151.05 mg/dl and TG=164.67 mg/dl). Treatment with Arogyavardhini significantly (P<0.05) reduces the increased levels of TC (160.123 mg/dl) and TG (189.5 mg/dl) in hyperlipedimic rats. Treatment with Zpter significantly (P<0.05) reduces the increased levels of TC (163.89 mg/dl) and TG (193.167 mg/dl) in hyperlipedimic rats, which is comparable to standard treatment atorvastatin (TC= 155.81 mg/dl, TG=180.33 mg/dl). Conclusion: The observations in this study suggest that, herbal formulations arogyavardhini and zpter have the potential to overcome hyperlipidemia.